The Manifestation of Wahdatul Adyan in Ibn Arabi's Perspective as a Basis of Religious Moderation in Indonesia - Miftakhur Rohman; Abdulloh Hanif (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2026)
Indonesia's profound religious, ethnic, and cultural diversity necessitates a robust framework for religious moderation to maintain national unity. However, public misunderstanding persists, particularly the erroneous equation of moderation with the claim that "all religions are the same." This study reinterprets the Sufi concept of Wahdatul Adyan (unity of religions) as developed in Ibn Arabi's thought (Futuhat al-Makkiyyah and Tarjuman al-Asywaq) to provide a more precise foundation for religious moderation. Using a qualitative document study approach and systematic literature review, this research analyzes Ibn Arabi's original texts and contemporary Indonesian discourse on religious moderation. The findings reveal that the popular understanding of Wahdatul Adyan as "religious unification" is a misinterpretation. Instead, the concept signifies the "unification of shared values across religions"—emphasizing common ethical principles such as compassion, justice, and respect for human dignity, without erasing theological differences. Consequently, religious moderation is reframed not as syncretism but as a collaborative effort to identify convergent moral values that foster interfaith harmony. This study contributes to the global discourse on religious moderation by offering a conceptually grounded, value-based alternative to both exclusivist and relativist approaches, with practical implications for multicultural societies, particularly in Southeast Asia.